2023
DOI: 10.3390/su15031760
|View full text |Cite
|
Sign up to set email alerts
|

Do Dynamic Capabilities and Digital Transformation Improve Business Resilience during the COVID-19 Pandemic? Insights from Beekeeping MSMEs in Indonesia

Abstract: This study investigated the influence of Dynamic Capabilities (DC) and Digital Transformation (DT) on Business Resilience During the COVID-19 Pandemic. Using cross-sectional data from 388 micro, small, and medium enterprises (MSMEs) of beekeeping in Indonesia. Furthermore, the data were analyzed by Structural Equation Model (SEM) analysis and executed by SmartPLS 3.0 software. The main results of this study indicate that DC plays an important role in improving MSMEs’ DT. However, the essential role of DT on fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 81 publications
0
28
0
6
Order By: Relevance
“…This study is limited to the research of dairy cattle farming in the business development centers located in East Java. Furthermore, this research has not yet proven the measurement of each business based on the scale of operations, as demonstrated by previous research (reference 11), which indicates that the size of businesses in terms of assets can show differences in the resilience of entrepreneurs when facing threats.…”
Section: Limitationmentioning
confidence: 71%
See 1 more Smart Citation
“…This study is limited to the research of dairy cattle farming in the business development centers located in East Java. Furthermore, this research has not yet proven the measurement of each business based on the scale of operations, as demonstrated by previous research (reference 11), which indicates that the size of businesses in terms of assets can show differences in the resilience of entrepreneurs when facing threats.…”
Section: Limitationmentioning
confidence: 71%
“…[1][2][3][4][5][6][7][8][9][10] . It can lead to entrepreneurs being unable to maintain their competitive advantages 11 , as several international studies have shown that when they cannot sustain, there is a decline in profit and business performance. For example, according to the empirical outcomes revealed by 12 conducted in the agricultural sector in the Netherlands, there is a connection between psychological issues and financial problems for entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%
“…It is remarkable, nevertheless, that a sizable percentage voiced worries regarding data privacy. This emphasizes how important it is for companies to be open and honest about data security and privacy concerns in their omnichannel initiatives [25]- [28].…”
Section: Discussionmentioning
confidence: 99%
“…The development of DC helps companies adapt to the waves of technological innovation through environmental scanning, sensing, and integrative stages (Putritamara et al, 2023). By developing sensing and seizing capabilities firms could take advantage of opportunities, and ultimately reconfigure and adapt the business to the future advances of upcoming digital technologies quickly.…”
Section: Dynamic Capabilitiesmentioning
confidence: 99%
“…Moreover, they found that the size effect of market agility is larger than the operational agility. In a recent study, Putritamara et al (2023) by using cross-sectional data from beekeeping companies in Indonesia, found that dynamic capabilities play an important role in improving the DT of SMEs.…”
Section: Dynamic Capabilitiesmentioning
confidence: 99%